P233 COVID-19-a ssociated Mucormycosis: an experience of invasive fungal sinusitis from a tertiary care referral center in Northern India. (20th September 2022) - Marak, Rungmei S K; Chaudhary, Radhika; Keshri, Amit Kumar; Baghel, Surendra Singh; Manogaran, Ravi Sankar; Dixit, Ajai Kumar; Mishra, Prabhakar
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objectives: The study was aimed to determine the patient demographics, risk factors, which include comorbidities, presenting symptoms and signs, medications used to treat COVID-19, species of Mucorales isolated, and the management outcome of COVID-19-associated mucormycosis. Methods: It was a 6-month retrospective, propensity score-matched, comparative study conducted at a tertiary care center, involving 124 patients with COVID-19 associated mucormycosis admitted between April and September 2021, who were suffering from or had a history of COVID-19 infection. Results: Among the 124 patients, 87 were male, and 37 were female. A total of 72.6% of patients received steroids, while 73.4% received antibiotics, and 55.6% received oxygen during COVID-19 management. The most common comorbidities were diabetes mellitus (83.9%) and hypertension (30.6%). A total of 92.2% had mucor, 16.9% had Aspergillus, 12.9% had both, and one patient had hyalohyphomycosis on fungal smear and culture. The comparative study showed the significant role of serum ferritin, glycemic control, steroid use, and duration in COVID-19-associated invasive fungal disease ( P  <.001). Headache and facial pain (68, 54.8%) were the most common symptoms. The most involved sinonasal site was the maxillary sinus (90, 72.6%). Direct KOH microscopy for fungus was positive in 100% of the cases, 82.2% were Mucorales; 12.9% showed mixed fungal hyphae (mucormycetes and Aspergillus spp.), 4% Aspergillus and hyaline septate non- Aspergillus fungus hyphae were seen in 0.8%. Mucoraceous fungi isolated were R. arrhizus, R. microsporus, R. homothallicus, Rhizomucor pusillus, and Leithemia corymbifera . The overall survival rate at the 3-month follow-up was 79.9%. Conclusion: COVID-19-related aggressive inflammatory response, uncontrolled glycemic level, and rampant use of steroids are the most important predisposing factors in developing COVID-19-associated invasive fungal sinusitis caused by Mucorales. A high index of suspicion, aggressive surgical and antifungal therapy resulted in the successful outcomes for most of the patients.